2014
DOI: 10.1183/09031936.00119714
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary survival analysis of individuals with cystic fibrosis: a cohort study

Abstract: Previously established predictors of survival may no longer apply in the current era of cystic fibrosis (CF) care. Our objective was to identify risk factors associated with survival in a contemporary CF population.We used the Canadian CF Registry, a population-based cohort, to calculate median age of survival and summarise patient characteristics from 1990 to 2012. Clinical, demographic and geographical factors, and survival were estimated for a contemporary cohort (2000-2012) using Cox proportional hazards m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
140
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 26 publications
7
140
0
6
Order By: Relevance
“…O conhecimento sobre as terapias pode trazer esperança para os pacientes com FC. Outro aspecto relacionado à doença é a esperança de maior sobrevida, que aumentou consideravelmente nas últimas décadas (Kuehn, 2014;Stephenson et al, 2015). Atualmente, pacientes com FC podem ter um estilo de vida normal, considerando as limitações do tratamento da doença.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O conhecimento sobre as terapias pode trazer esperança para os pacientes com FC. Outro aspecto relacionado à doença é a esperança de maior sobrevida, que aumentou consideravelmente nas últimas décadas (Kuehn, 2014;Stephenson et al, 2015). Atualmente, pacientes com FC podem ter um estilo de vida normal, considerando as limitações do tratamento da doença.…”
Section: Discussionunclassified
“…Este sentimento de esperança, que pode envolver a busca de uma cura, é diferente de negação, porque ela não afeta o ajuste para o processo da doença, e é compatível com a aceitação da realidade e adesão ao tratamento (Stephenson et al, 2015).…”
Section: Discussionunclassified
“…The dynamic nature of the CF population has been highlighted by significant improvements in survival (5,14). U.S. data have demonstrated that CF survival improved from 2000 to 2010 at a rate of 1.8%/year, and a median survival of 56 years is projected if the mortality rate continues to decrease at the rate observed between 2000 and 2010 (5).…”
Section: Epidemiology and Changing Demographicsmentioning
confidence: 99%
“…Advances achieved over the last four decades have transformed CF from a fatal childhood disease to a long-term chronic condition. CF patients can now reach adulthood [2][3][4][5], although most of them still have a reduced life expectancy, and the adult population has passed from 44.55% in 2005 to 49.3% in 2010 (figure 1), the oldest patient being aged >80 years, from the 2010 European CF registry [6]. In the near future, even though CF paediatric care will remain crucial to assure the best growth for patients and transition to adulthood, CF centres may largely be considered as adult oriented [7], and we should, therefore, aim for the new concept of active and healthy ageing (AHA) in CF patients.…”
mentioning
confidence: 99%